2005
DOI: 10.1016/j.jasms.2005.02.025
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of small molecules by ultra thin-layer chromatography-atmospheric pressure matrix-assisted laser desorption/ionization mass spectrometry

Abstract: The feasibility of ultra thin-layer chromatography atmospheric pressure matrix-assisted laser desorption ionization mass spectrometry (UTLC-AP-MALDI-MS) has been studied in the analysis of small molecules. Because of a thinner adsorbent layer, the monolithic UTLC plates provide 10 -100 times better sensitivity in MALDI analysis than conventional high performance thin-layer chromatography (HPTLC) plates. The limits of detection down to a low picomole range are demonstrated by UTLC-AP-MALDI-MS. Other advantages … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 41 publications
1
33
0
Order By: Relevance
“…The authors do not report any plate height measurements. An emerging use of monolithic layers is in mass spectrometry where an increase in mass detection limits of an order or magnitude or more have been obtained using matrix-assisted laser desorption ionization (MALDI) [86,87] and surface desorption electrospray ionization techniques [88] compared with high performance stabilized particle layers. These improvements result mainly from a reduction in the layer thickness rather than an increase in separation performance.…”
Section: Monolithic Filmsmentioning
confidence: 99%
“…The authors do not report any plate height measurements. An emerging use of monolithic layers is in mass spectrometry where an increase in mass detection limits of an order or magnitude or more have been obtained using matrix-assisted laser desorption ionization (MALDI) [86,87] and surface desorption electrospray ionization techniques [88] compared with high performance stabilized particle layers. These improvements result mainly from a reduction in the layer thickness rather than an increase in separation performance.…”
Section: Monolithic Filmsmentioning
confidence: 99%
“…Thus, it seems reasonable to assume that a reduced thickness of the stationary phase would enhance the detectability of the complete analyte. Thus, standard TLC plates were replaced by ultra-thin-layer chromatography (UTLC) plates (Salo et al 2005) and it could be shown that due to the thinner adsorbent layer the monolithic UTLC plates provide 10-100 times better sensitivities. Although the majority of commercially available MALDI devices use high vacuum conditions, atmospheric pressure (AP) MALDI is increasingly used for two reasons: (a) these devices are less accident-sensitive and (b) provide the capability to record collisionally induced (CI) fragment ion spectra without the need of an extra collision cell.…”
Section: Pharmaceuticalsmentioning
confidence: 99%
“…Moreover, the TLC plate size is not limited by the dimensions of a vacuum chamber. Techniques, such as electrospray ionization (ESI) [17], [18], [19], electrospray-assisted laser desorption ionization (ELDI) [20], desorption electrospray ionization (DESI) [21], laser desorption/atmospheric pressure chemical ionization (LD-APCI) [22], atmospheric pressure matrix-assisted laser desorption/ionization (AP-MALDI) [23], [24] and direct analysis in real time (DART) [25], [26] have been adopted to generate mass spectra of compounds directly from TLC plates.…”
Section: Introductionmentioning
confidence: 99%